BINGE EATING DISORDERS; UPDATED AND EMERGING APPROACHES - TEAIMA, MAHMOUD; HAMID, MAGDI M. ABDEL; SHOMAN, NABIL A.; JASTI, BHASKARA R.; EL-NABARAWI, MOHAMED A.; YASSER, MOHAMED (International Journal of Applied Pharmaceutics, 2021)
Objective: Binge eating disorders (BED) recently become a global health care issue for clinicians with detrimental effects on all organ systems. A multidisciplinary strategy including pharmacotherapy is required for its management. Methods: This review is intended to comparatively evaluate the relative efficacy of different pharmacological agents in BED treatment with new therapeutic approaches, focusing on the clinical evidence and on Phase III randomized controlled trials. Results: Data suggest that certain treatments have advantages over placebos to reduce binge eating features; however, the small duration of such research with the lack of adequately sized trials was the major limitation in interpreting these findings. Furthermore, these medications are mostly not greatly efficient for BED associated with obesity except for topiramate, which markedly improves the features of binge episodes with weight loss. Till now, lisdexamfetamine is still the only drug with regulatory permission for BED therapy; however, its weight loss efficacy has not been established. Conclusion: Drugs alone or in combination approaches may be useful pharmacotherapies to yield promising outcomes acutely and over longer-term follow-up in the treatment of BED.